Association of On-Admission Anemia With 1-Year Mortality in Patients Hospitalized With Acute Heart Failure: Results From the HERO Study - Li, Junlei; Jiang, Chao; Lai, Yiwei; Li, Li; Zhao, Xiaoyan; Wang, Xiaofang; Li, Ling; Du, Xin; Ma, Changsheng; Dong, Jianzeng (Frontiers in Cardiovascular Medicine, 2022)
Background Anemia is common in patients with chronic heart failure (HF) and is associated with adverse outcomes. However, data regarding the prognostic value of on-admission anemia on mortality in patients hospitalized with acute HF were relatively limited and conflicting. This study aimed to investigate the association of on-admission anemia with 1-year mortality and evaluate whether anemia is an independent predictor of mortality in patients hospitalized with acute HF. Methods The present analysis included 4,244 patients hospitalized with acute HF from the HERO (Heart Failure Registry of Patient Outcomes) study. On-admission anemia was defined using the World Health Organization (WHO) criteria (hemoglobin <120 g/L in women and <130 g/L in men). Cox proportional hazards models were used to assess the association of anemia with 1-year all-cause and cardiovascular mortality. Results Of 4,244 patients, 2,206 (52.0%) patients had no anemia, 1,106 (26.1%) patients had mild anemia (men 110 ≤ hemoglobin < 130 g/L; women 110 ≤ hemoglobin < 120g/L), and 932 (22.0%) patients had moderate-to-severe anemia (hemoglobin < 110 g/L). After a median follow-up of 12.4 months (interquartile range: 11.9, 12.6), 867 (20.4%) patients died. Among the 742 (85.6%) deaths with confirmed causes, 664 (89.5%) were due to cardiovascular diseases. The mortality rates in patients with no anemia, mild anemia, and moderate-to-severe anemia were 16.6%, 20.4%, and 29.4%, respectively (p < 0.001). The association of anemia with increased all-cause mortality was significant in the unadjusted model (hazard ratio [HR]: 1.54, 95% confidential interval [CI]: 1.35–1.77, p < 0.001), and remained statistically significant after adjustment for most potential confounders (HR: 1.20, 95%CI: 1.03–1.40, p = 0.020), but no longer significant after additional adjustment for natriuretic peptides (HR: 1.02, 95%CI: 0.86–1.21, p = 0.843). When considering the degree of anemia, moderate-to-severe anemia was an independent predictor of all-cause mortality after full adjustment (HR:1.26, 95%CI: 1.03–1.54, p = 0.028), whereas mild anemia was not (HR: 0.84, 95%CI: 0.69–1.04, p = 0.104). A similar relationship was also found between anemia and cardiovascular mortality. Conclusions On-admission anemia, defined by the WHO criteria, is not an independent predictor of mortality in patients hospitalized with acute HF. Moderate-to-severe anemia in patients with acute HF is independently associated with increased mortality.